Modern art and the life of a culture : the religious impulses of modernism - Anderson, Jonathan A., 1977-; Dyrness, William A. (Downers Grove, Illinois : IVP Academic, and imprint of InterVarsity Press, 2016)
For many Christians, engaging with modern art raises several questions: Is the Christian faith at odds with modern art? Does modernism contain religious themes? Nearly fifty years ago, Dutch art historian and theologian Hans Rookmaaker offered his answers to these questions when he published his groundbreaking work, Modern Art and the Death of a Culture. While appreciating Rookmaaker's invaluable contribution to the study of theology and the arts, this volume-coauthored by an artist and a theologian-responds to his work and offers its own answers to these questions by arguing that there were actually strong religious impulses that positively shaped modern visual art. This book, the first in IVP Academic's new Studies in Theology and the Arts series, brings together the disciplines of art history and theology and points to the signs of life in modern art.
Part 1. Critical contexts. Introduction: religion and the discourse of modernism -- H.R. Rookmaaker, Modern art and the death of a culture -- Part 2. Geographies, histories and encounters. France, Britain and the sacramental image -- Germany, Holland and northern romantic theology -- Russian icons, Dada liturgies and rumors of nihilism -- North America and the expressive image -- North America in the age of mass media.
Includes bibliographical references (pages 339-360) and index.
Keywords: Modernism (Art) -- Themes, motives; Christianity and art; Rookmaaker, H. R. -- 1922-1977.